2019
DOI: 10.1007/s12273-019-0531-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exterior convective heat transfer coefficient models on the energy demand prediction of buildings with different geometry

Abstract: Accurate models for exterior convective heat transfer coefficients (CHTC) are important for predicting building energy demand. A detailed review of the literature indicates that existing CHTC models take into account the impact of building geometry either incompletely, or not at all. To the best of our knowledge, research on the impact of exterior CHTC models on the predicted energy performance of buildings with different geometry has not yet been performed. This paper, therefore, investigates the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 64 publications
0
7
0
2
Order By: Relevance
“…Another important aspect that deserves further attention is the influence of the wind flow on the heat dissipation conditions in BIPV elements. As research on wind flow in the built environment progresses, new insights on how the wind affects the convective heat dissipation in buildings have been published (Emmel et al, 2007;Defraeye et al, 2011;Mirsadeghi et al, 2013;Montazeri et al, 2015;Montazeri & Blocken, 2017Iousef et al, 2019). In particular, it has been demonstrated that convective heat transfer coefficients resulting from wind effects not only vary over the building surfaces, but also depend on the building geometry (Montazeri et al, 2015;Montazeri & Blocken, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect that deserves further attention is the influence of the wind flow on the heat dissipation conditions in BIPV elements. As research on wind flow in the built environment progresses, new insights on how the wind affects the convective heat dissipation in buildings have been published (Emmel et al, 2007;Defraeye et al, 2011;Mirsadeghi et al, 2013;Montazeri et al, 2015;Montazeri & Blocken, 2017Iousef et al, 2019). In particular, it has been demonstrated that convective heat transfer coefficients resulting from wind effects not only vary over the building surfaces, but also depend on the building geometry (Montazeri et al, 2015;Montazeri & Blocken, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in (Susorova et al, 2013), some studies showed a decrease in values of convective heat transfer coefficients for a wide range of vegetated façade types, the present findings through the (Ayata et al, 2011; ASHRAE, 2020) methods are in accordance with this trend. It is known that the building geometry, surroundings and wind directions have a significant effect on the magnitude of the convective heat transfer coefficient (Defraeye et al, 2011;Iousef et al, 2019). Several correlations are based on the results of flat plate experiments in wind tunnels (Jayamaha et al, 1996) and may not fully capture the local variations of geometry and wind directions around the building façades.…”
Section: Impact Of Convective Heat Transfer Coefficientmentioning
confidence: 99%
“…Bu kayıp ve kazançlar bina cephe elemanlarının özellikleri ile doğrudan ilişkilidir. Bina cephesi, bina enerji verimliliği ve iç termal konfor ihtiyacının karşılamasında çok önemli bir rol oynamaktadır [10,11]. Bina cephesi, iç-dış ortamlar arasında karmaşık bir arayüzdür [11].…”
Section: Giriş (Introduction)unclassified
“…Bina cephesi, bina enerji verimliliği ve iç termal konfor ihtiyacının karşılamasında çok önemli bir rol oynamaktadır [10,11]. Bina cephesi, iç-dış ortamlar arasında karmaşık bir arayüzdür [11]. Bina kabuğunu meydana getiren pencere-duvar oranı, insan deneyimini çeşitli şekillerde etkileyen bir tasarım özelliğidir [12].…”
Section: Giriş (Introduction)unclassified